Liquidity Risk Management And Financial Performance In Malaysia: Empirical Evidence From Islamic Banks - Mohd Ariffin, Noraini (Aceh International Journal of Social Science, 2012)
Abstract - Liquidity risk arises from maturity mismatches where liabilities have a shorter tenor than assets. A sudden rise in the borrowersâ demands above the expected level can lead to shortages of cash or liquid marketable assets (Oldfield and Santamero, 1997). This paper aims to analyse the liquidity risks and disclosure as well as to draw the relationship between liquidity risks and financial performance measures using return on assets (ROA) and return of equity (ROE) of the Islamic banks. Based on selected Islamic banks in Malaysia over the period from 2006 to 2008, the study also attempts to determine the impact of the global financial crisis on the Islamic banksâ liquidity risks and financial performance. Findings of the study contribute towards enriching the literature on the risk management of the Islamic banks by providing deeper understanding on issues relating to liquidity risk management by the Islamic banks.